(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with a comparative research of William Faulkner «Go down Moses» and Valeriy Shevchuk «Pryvyd Mertvoho Domu» («The Ghost of the Dead House»). Their typological similarity and at the same time art originality were grounded. There was demonstrated the realization of life events into special genre form in which the unity was created not owing to penetrating plot but first of all in free development of common theme and uniting idea.